Teaching Vocabulary by Using Total Physical Response - Devi Fadiana; Syamsul Bahri Ys; Nurul Inayah (Research in English and Education Journal, 2020)
This study aimed at finding out whether there is any improvement of students’ vocabulary mastery after being taught by vocabulary using Total Physical Response (TPR) in SD Swasta Pertiwi Sabang. This experimental research was conducted by giving the students a pretest before the treatments and a posttest after the treatments. The population of this research was the whole students at SD Swasta Pertiwi Sabang there are 75 students. The samples of this study were the students from fourth grade students which were chosen by using random sampling consist of 23 students. Total Physical Response can be used to teach vocabulary in Elementary School. The result revealed that there was a significant improvement of students’ vocabulary mastery after being taught by using Total Physical Response. The mean score from the pretest increase 53.81 points and in the posttest are 81.74. The t-test value was also found higher than the t-table (ts= 13.777 tt= 2.080). It means the alternative hypothesis (Ha) is accepted whereas the null hypothesis (Ho) is rejected.